Concentration and temporal variability of nitrogen, phosphorus and zinc in pecan leaves - Frusso, Enrique; Lavado, Raul Silvio; Insausti, Pedro; Cipriotti, Pablo Ariel (International Society for Horticultural Science, 2019)
I International Symposium on Pecans and Other Carya in Indigenous and Managed Systems